Kajian Efektivitas Program Corporate Social Responsibility (CSR) Yayasan Unilever Indonesia - Irwanto, Abdul Kohar; Prabowo, Angga (Jurnal Manajemen, 2009)
Since the year of 2000 until 2007, PT Unilever Indonesia Tbk has put in place the CSR program into the working agenda of the company from the corporate structure through the whole related business part. The company has been emphasizing the effort to achieve the better prosper of public quality of life. The main objective of the research is to understand the effectiveness of the CSR program of Unilever Indonesia Foundation as part of the CSR program definition which so far has been conducted and in order to compare the CSR program among other similar companies. The information and data that has been collected within this research are covering both the primary and secondary data based on the date of August 2008 to October 2008. The method of the analysis are using the descriptive analysis and Rank Spearman correlation analysis. Based on the research, to conclude, there are three CSR program operated by the Unilever Indonesia Foundation which include environmental program, recycling, and education. Based on the regression analysis, the results show the factors affecting the environmental program that are including organizational issue and priority of needs. As for the recycle program, the factors that affect the effectiveness of the CSR program are the party who receive the support and organizational issue. Additionally, the education program is mainly driven by the priority of needs.Keywords: Effectiveness, Corporate Social Responsibility, Environmental Preservation.